Enhancing biosensor properties of conducting polymers via copolymerization: Synthesis of EDOT-substituted bis(2-pyridylimino) isoindolato-palladium complex and electrochemical sensing of glucose by its copolymerized film - KOCA, ATIF (ELSEVIER ADVANCED TECHNOLOGY, 2017)
1,3-Bis(2-pyridylimino)isoindoline derivative bearing 3,4-ethylenedioxythiophene (EDOT-BPI) and its palladium complex (EDOT-PdBPI) were synthesized and characterized by FT-IR, H-1 NMR, C-13 NMR, UVVis spectroscopies and via mass spectrometric analysis. Polymerization of EDOT-PdBPI and copoly-merization with 4-amino-N-(2,5-di(thiophene-2-yl)-1H-pyrrol-1-yl)benzamide (HKCN) were carried out by an electrochemical method. In addition, P(EDOT-PdBPI-co-HKCN) modified graphite rod electrode was improved for amperometric glucose sensor based on glucose oxidase (GOx). In this novel biosensor matrix, amino groups in HKCN were used for the enzyme immobilization. On the other hand, EDOT-PdBPI used to mediate the bioelectrocatalytic reaction. Amperometric detection was carried out following oxygen consumption at -0.7 V vs. the Ag reference electrode in phosphate buffer (50 mM, pH 6.0). The novel biosensor showed a linear amperometric response for glucose within a concentration range of 0.25 mM to 2.5 mM (LOD: 0.176 mM). Amperometric signals at 1 mM of glucose were 17.9 mu A under anaerobic conditions. Amperometric response of the P(EDOT-PdBPI-co-HKCN)/GOx electrode decreased only by 13% within eight weeks. The P(EDOT-PdBPI-co-HKCN)/GOx electrode showed good selectivity in the presence of ethanol and phenol. This result shows that, modification of the proposed biosensor by copolymerization of amine functionalized monomer, which is indispensable to the enzyme immobilization, with palladium complex bearing monomer, which is mediate the bioelectrocatalytic reaction, have provided to give perfect response to different glucose concentrations. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: 1,3-bis(2-pyridylimino)isoindoline; Palladium; Conducting polymer; Glucose; Electropolymerization; Glucose biosensors; CATALASE MIMICS; LIGANDS; 1,3-BIS(2'-PYRIDYLIMINO)ISOINDOLINE; PHTHALOCYANINES; IMMOBILIZATION; POLYMERIZATION; MATRIX; UNITS